Europeans travel behaviour in Istanbul and Turkey - Ebru Kerimoglu (European Regional Science Association (ERSA), 2004)
The trends and developments in the tourism industry show that the touristic activities are among the most significant economic and social facts of the 20th century. The Europe preserves its stake in the developing tourism sector of the world. The countries of the European Union do have a position in the lead as far as the international tourist circulation is concerned, in the form of primary resource and major destination. The citizens of the European Union also represent a considerable market for the countries seeking to have a place on the global tourism markets. Most of the international visitors to Turkey are from European Union, who also represents a significant potential for Turkish tourism. This study examines the holiday making ratios, profiles, demands and behaviors of the European Union travelers and gives an analysis and assessment of such considerable potential. Turkey is a special location in the world with regard to its cultural inheritance while Istanbul is its major city in relation with international connections. Istanbul's significant role in history with its dynamic geographical position and its traditional architecture and the civilizations hosted by the city would well cause Istanbul's being worthy of a share its deserves from the global tourism market and the tourism functions, that is considered to be most efficient tool in marketing Istanbul, has a significance in the city's position and future. Istanbul has various urban spaces in the form of touristic products. For providing the development in relation with certain strategies of tourism planning, the demands and preferences of the travelers to Istanbul should be determined. Analyzing the visitors from that point of view has a considerable importance for the potential visitors of the city while planned development shall provide the opportunity to obtain the guiding data. In the light of these data, determining the planning strategies for Istanbul and developing the recommendations that could be used for a tourism plan for sustainable tourism supported by tourism policies in both public and private sectors and planners are very significant. This study focuses on the visitors from European Union and evaluates their trends and behaviors while making deductions from the potentials they own. The study gives the holiday periods of the Europeans, their length of stay in the destinations, the number of persons attending travels, the destinations they prefer, the transportation modes they use, travel organizations as well as the problems they face, and in that parallellity the characteristics of the European Union citizens visiting Turkey and Istanbul were analyzed with comparisons. In conclusion, the general vacation trends and behaviors of the European Union citizens and their relations with the experiences they face in Turkey is very considerable with the current and potential evaluations in the European market which in fact is very important for Turkey.
Keywords: 330